Tradition of Tetesan in Central Java - Andini Resita Dewi (Universitas Muhammadiyah Malang, 2024)
One of the traditions in Java in the life cycle is the tradition of dripping or female circumcision, especially at the age of 8-12 years. The various meanings of this dripping tradition are, for example, a sign of maturity, avoiding bad things and getting good fortune. At present, the dripping tradition has been abandoned by many Javanese people. Moreover, there is some information that drops are not good for health. However, this tradition must be maintained and preserved. The purpose of this study is to find out an overview of the dripping tradition in Central Java, especially Central Java and Yogyakarta. Moreover, there are differences in the implementation of the drip for ordinary people and the Yogyakarta Palace. The research method used is the historical method. As expressed by Kuntowijoyo in his book Introduction to History which states that the historical research method has five stages, namely topic selection, heuristics (source gathering), source criticism (verification, interpretation, and historical writing (historiography). The results of this study are how practice is the tradition of dripping in Central Java, namely Central Java and Yogyakarta, especially for ordinary people and the Yogyakarta Palace. The procedures for ordinary people are relatively ordinary while at the Yogyakarta Palace it is classified as complex because there are rules. And also, this drip is included in the oral tradition because it is tied to beliefs, meanings, symbols, norms, and customs that describe the meaning of this dripping tradition.